PENGARUH VARIASI LAMA KONTAK TANAMAN MELATI AIR (ECHINODORUS PALAEFOLIUS) DENGAN SISTEM SUBSURFACE FLOW WETLANDS TERHADAP PENURUNAN KADAR BOD, COD DAN FOSFAT DALAM LIMBAH CAIR LAUNDRY - Amalia Safira Koesputri; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2016)
Laundry waste contains high BOD, COD, and phosphate, but the waste is directly disposed into sewerage without treatment. The checking result of BOD, COD, and phosphate of laundry wastewater is 326 mg/l, 1157 mg/l, and 14 mg/l This number is exceed the standard of Perda Jateng No 5 tahun 2012. Mexican-Sword Plant (Echinodorus palaefolius) is an aquatic plant that has potential as pereduktor contaminants .The purpose of this research was to find out effects of detention time variation mexican-sword plant (echinodorus palaefolius) toward BOD, COD and phospat level. This research is using experiment with pretest-posttest design. The statistic test that used is One Way Anova and Kruskal Wallis. The results show an average reduction of BOD concentration with detention time 2 days was 84.96%, detention time 3 days was 84.23%, detention time 4 days was 87.78%, detention time 5 days was 90%, detention time 6 days was 88.91%, and detention time 7 days detention time 88.52%. COD concentration with detention time 2 days was 85.22%, detention time 3 days was 85.47%, detention time 4 days was 88.7%, detention time 5 days was 90.79%, detention time 6 days was 84.93 %, and detention time 7 days was 89.31%. Phosphate concentration with detention time 2 days was 52.35%, detention time 3 days was 14.31%, detention time 4 days was 51.33%, detention time 5 days was 56.35%, detention time 6 days was 42.72 %, and detention time 7 days was 44.69%. The different test result of BOD (Sig 0.741) and COD (Sig 0836) shows there are no average difference reduction levels of BOD and COD among detention time variation. While the result of phosphate (Sig 0024) shows there are an average difference between detention time variation. The highest percentage is in 5 days. Further research is needed to use the system continuously to be applied according to the existing field conditions.